Convergence of per capita ecological footprint among BRICS-T countries: evidence from Fourier unit root test - Bayraktar, Yuksel; Koc, Kenan; Toprak, Metin; Ozyilmaz, Ayfer; Olgun, Mehmet Firat; Balsalobre-Lorente, Daniel; Soylu, Ozgur Bayram (Springer Heidelberg, 2023)
In recent years there has been a great deal of research into environmental pollution using a variety of techniques in response to growing environmental concerns. Convergence analysis, one of these techniques, helps determine whether the developing countries will catch up with the rich countries in pollution using unit root tests. However, the vast majority of the research in the field has generally used conventional unit root tests. Since many economic series contain structural breaks, using unit root tests that account for structural breaks is essential for accurate prediction. More specifically, if the series has a fractional process, conventional unit root tests may erroneously conclude that the departure from linearity is permanent. Moreover, the existing literature mainly uses gas emissions, such as carbon dioxide, which represent pollution weakly. Therefore, we use per capita ecological footprint (EF hereafter) as a more comprehensive pollution indicator of environmental degradation. In this direction, the study aims to determine whether BRICS-T countries' EF converges to the average of the BRICS-T for the 1992-2017 period. Besides the ADF unit root test, we employed the Fourier ADF unit root test, which considers the structural breaks, and the Fractional Frequency Fourier ADF unit root test, which accounts for structural breaks by considering fractional values. Our results showed that EF converges in Russia and Turkey according to the conventional ADF test, in China and Russia according to the Fourier ADF test, and in Brazil and China according to the Fractional Fourier Frequency test.
Keywords: Ecological Footprint; Convergence; Unit Root Test; Brics-T; Carbon-Dioxide Emissions; Co2 Emissions; Club Convergence; Growth; Stationarity; Capacity; Middle; Form